„Because he wanted to have this book in his house” – colophon in a 14th century Serbian manuscript as a source for research on the distribution of the chronicle of George the Monk called Hamartolus in the South Slavic writings - Brzozowska, Zofia A. (Balcanica Posnaniensia. Acta et studia, 2025)
The aim of this article is to present a previously unpublished source, i.e. an extended colophon, placed on the last pages of a Serbian manuscript from 1385/1386 (ГИМ, Син. 148, fol. 433–434). This manuscript is one of the oldest copies of the second translation into Church Slavic of the chronicle of George the Monk called Hamartolus (9th century), known as Лѣтовникъ. This translation was based on the version of the Byzantine historian’s work, which most likely has not survived to this day in any Greek manuscript. The translation was made in the Second Bulgarian Empire, in the first half of the 14th century, and then became popular in the Slavic monastic environment on Mount Athos, in Nemanjić’s Serbia and in the Danubian principalities. Лѣтовникъ can also be considered one of the least studied versions of the chronicle of George the Monk. The manuscript ГИМ, Син. 148 was written – as we read in the colophon – by two monks, Roman and Basil, in the Serbian monastery of Hilandar on Mount Athos, on the order of Radovan, a magnate from the circle of Constantine Dejanović Dragaš, for the needs of his private book collection. The text presented here is therefore an interesting testimony to the spread of reading culture in the Balkans in the 14th–15th centuries.